KINERJA PENYULUH PERTANIAN LAPANGAN DAN TINGKAT KEPUASAN PETANI JAGUNG DI BPPP KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Ade Fitriyani; Tubagus Hasanuddin; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This research aims to know corn productivity level in the working area of the extension center (BPPP) Natar Subdistrict, the level of Agricultural Extension Workers (AEWs) in the BPPP, factors related to the level of the performance of AEWs, the level of satisfaction of corn farmers on the performance of AEWs, and  the relationship between the level of performance of AEWs and the level of satisfaction of corn farmers.  Research conducted in BPPP Natar Subdistrict, South Lampung Subdistrict uses a survey method.  The sample in this study consisted of eight AEWs and 54 corn farmers.  Data analysis method uses a descriptive method and Rank Spearman correlation.  The results showed the average level of corn farming productivity in the Natar Subdistrict is 6,49 tons/ha.  The performance of AEWs is good.  The factors related to the performance of AEWs are the age of the AEWs, working period of the AEWs, and availability of facilities and infrastructure.  The level of satisfaction of corn farmers on the performance of AEWs in Natar Subdistrict is moderately satisfied, and the level of performance of AEWs has a significant relationship with the level of satisfaction of corn farmers in the Natar Subdistrict. Key words: agriculture extension workers, farmer satisfaction, performance